Judicial and administrative guarantees of equal treatment at work in Law 15/2022 - González del Rey Rodríguez, Ignacio (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
Law 15/2022, of July 12, for equal treatment and non-discrimination, does not directly modify any labor regulations, but indirectly affects some principles and rules of labor law. This paper analyzes the incidence of Law 15/2022 on labor regulation. In particular, the disagreements in relation to the judicial and administrative guarantees of equal treatment and non-discrimination at work. First, in the legal framework. Secondly, in the principles and preventive rules. Thirdly, in the administrative guarantees and penalties procedures (administrative and disciplinary). Finally, in court proceedings (enlarged procedural ability, precautionary or preservation measures, distribution of burden of proof, shared responsibilities and compensation for damages, especially moral).
Keywords: equality and non-discrimination at work; administrative penalties procedure; procedure for protection of fundamental rights in labour courts